Analysis of power losses and Lifetime for the inverter in electric Vehicles using variable voltage Control and variable switching Frequency modified pwm - Anas Ayed, Sharif Ibrahim (2020)
With the increasing demand for reduced emissions and improved fuel economy, the automakers are focusing on the development of electric vehicles (EVs). The performance requirements for EVs includes high driving range and long life of its components. The power converters are among the most stressed and less reliable EV drivetrain components. Hence, improving the lifetime of the power converters is essential for the success of EV adoption. The lifetime of the power converters can be improved by reducing thermal stress of the power devices, which represents the main cause of failure. Since the temperature and power losses of the power device are proportional, thermal stress can be reduced by minimizing the power losses. In addition to the lifetime improvement, minimizing the power losses of the power converters can extend the EV range since the power demand under a given loading conditions is reduced. In this regard, this thesis aims to study the impact of an existing power loss reduction technique known as variable dc-bus voltage control (VVC) on the inverter lifetime. In addition, it proposes a new pulse width modulation (PWM) strategy called variable switching frequency modified PWM (VSF-MPWM) for three-phase two level voltage source inverter. The VSF-MPWM aims to minimize the inverter power losses, but without sacrificing the output current quality. In order to study the impact of the VVC on the inverter lifetime, a lifetime estimation method is first presented. This method uses the Artemis urban and US06 driving cycles in order to obtain the thermal loading, and consequently the lifetime consumption of the inverter power devices. Then, the VSF-MPWM is proposed, which minimizes the switching loss by clamping any of the three-phase legs at the phase current peak and by reducing the number of commutations through variable switching frequency. However, in order to achieve an acceptable current quality, the proposed VSF-MPWM controls both the clamping period and the switching frequency according to the current quality constraints of the conventional PWM strategy. The impact of the VVC on the inverter lifetime and the performance of the proposed VSF-MPWM on the inverter power losses and current quality are investigated through MATLAB Simulink. The lifetime analysis reveals that the VVC has the ability to improve the lifetime of the inverter by a factor of 5.06 and 3.43 under Artemis urban and US06 driving cycles, respectively, compared to the conventional constant dc-bus voltage control (CVC). On the other hand, the simulation result shows that the proposed VSF-MPWM can save up to 35.4 % and 23.8 % of switching and power losses, respectively, compared to the conventional PWM. Meanwhile, the VSF-MPWM can obtain the same output current quality as that of the conventional PWM.